(3GSGSjGJ haSjhdhLjG GdMVQ eY GSJYQGV deTGcd dGfJGL GdaSjhdhLjG hhSGFd GdMO ef CVQGQgG (B/s - (3MSf, YHOGdefYe CMeOs ((3GdbGgQI(B: s (3GdecJHI GdGcOejI(B, s, 1997)
(3jJfGhd gPG GdcJGH GdeTGcd GdRQGYjI GdJj bO JfTC Yf GdGfLQGa aj GdYhGed GdHjFjI LhjI cGfJ Ch GQVjI hGdYjhH GdajSjhdhLjI hJWhQGJ Gdfeh GdfHGJj WHjYjG cGf Ce ZjQ WHjYj , eY efGbTI cGaI GdYhGed GdeDKQI aj GdfHGJGJ aj LejY MGdGJg eY TQM ddLhGfH GdJWHjbjI heG jecf GJNGPg ef GLQGAGJ ddhUhd Edi Gdfeh GdeQZhH ajg hJLfH GdeTGcd GdaSjhLjI ZjQ GdeQZhH ajgG (B.s
Keywords: (3GdLZQGajG GdHTQjIs